Colostrum Avoidance Practices and Its Associated Factors among Mothers of Children Aged Less Than 12 Months in Jinka Town, South Ethiopia, 2020. A Community Based Cross Sectional Study - Elias Amaje; Feleke Gebremeskel; Girma Tufa; Miesa Gelchu; Zelalem Jabessa Wayessa (SAGE Publishing, 2022)
Background Even though colostrum discarding hurts child health, little is known about the extent of the problem and its contributing factors in Southern Ethiopia. This study aimed to determine the prevalence of colostrum avoidance practices and associated factors among mothers of children aged less than 12 months in Jinka town, South Ethiopia. Methods A community-based cross-sectional study was conducted at Jinka Town from March 1 to 30, 2020. A total of 420 mothers having children less than 12 months of age were selected by systematic sampling technique. The data were collected by using pretested interviewer-administered and semi-structured questionnaires. The data was entered using EPI DATA 3.1 and exported to SPSS version 23 for analysis. Descriptive statistics, binary and multivariable logistic regression analysis were done. Adjusted odds ratio with 95% CI at a p-value < 0.05 was estimated to identify statistically significant variables with colostrum avoidance practices. Results The prevalence of colostrum avoidance practice was 9.8% [95% CI: (6.9-12.5)]. Delayed initiation of breastfeeding [AOR = 9.08(95% CI 4.16-19.83)], lack of breastfeeding counseling [AOR = 2.33(95% CI 1.11-4.87)], home delivery of index child [AOR = 2.48 (95% CI 1.16-5.27)] and poor knowledge on breastfeeding [AOR = 4.55(95% CI 1.95-10.63)] were factors associated with colostrum avoidance practices. Conclusion Colostrum avoidance practice among mothers of children aged less than 12 months in Jinka town was high. Delayed initiation of breastfeeding, lack of breastfeeding counseling, home delivery, and knowledge of breastfeeding practice were factors associated with colostrum avoidance practice.